Analyzing Product Defects in the Production Process of Tempeh Using the FTA and FMEA Methods at CV. Aderina - Moch. Nuruddin; Adi Dharma (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
CV. Aderina is a Home Industry that produces tempeh has a product quality problem that is still found defective products. The types of product defects that often occur are foreign object entry, blackish color, and maturity level. A very effective method to overcome these problems is the FTA (Fault Tree Analysis) and FMEA (Failure Mode and Effects Analysis) methods. The purpose of this research is to identify the types of defects and factors that cause the highest defects in tempeh products and provide recommendations for improvement to improve the quality of Tempe products. Foreign body entry is the highest type of tempeh product defect in October 2021 based on the Pareto diagram with the number of defective products, namely 356 pcs and a defect percentage of 47.72%. In the Fault Tree of foreign object entry, the causes of defects that occur are caused by tools, human error, and the environment. Based on the FMEA method, the highest RPN value is obtained, namely the cause of defects in a less clean room with an RPN value of 189 and becomes a priority for improvement. CV. Aderina adalah Home Industry yang memproduksi tempe memiliki masalah kualitas produk yaitu masih ditemukan produk yang cacat. Adapun jenis cacat produk yang sering terjadi yaitu kemasukan benda asing, berwarna kehitaman, dan tingkat kematangan. Metode yang digunakan untuk mengatasi permasalahan tersebut adalah metode FTA (Fault Tree Analysis) dan FMEA (Failure Mode and Effects Analysis). Tujuan dilakukannya penelitian ini ialah untuk mengidentifikasi jenis kecacatan dan faktor penyebab kecacatan paling tinggi pada produk tempe serta memberikan rekomendasi perbaikan untuk meningkatkan kualitas produk Tempe. Kemasukan benda asing merupakan jenis kecacatan produk tempe yang tertinggi pada bulan Oktober 2021 berdasarkan diagram Pareto dengan jumlah produk yang cacat yakni 356 pcs dan persentase cacat sebesar 47,72 %. Berdasarkan Fault Tree kemasukan benda asing, penyebab kecacatan yang terjadi adalah disebabkan oleh tools, human error, dan lingkungan. Berdasarkan metode FMEA, didapatkan nilai RPN paling tinggi yaitu pada penyebab kecacatan ruangan kurang bersih dengan nilai RPN sebesar 189 dan menjadi prioritas perbaikan.